2019
DOI: 10.3390/life9030066
|View full text |Cite
|
Sign up to set email alerts
|

The Informational Substrate of Chemical Evolution: Implications for Abiogenesis

Abstract: A key aspect of biological evolution is the capacity of living systems to process information, coded in deoxyribonucleic acid (DNA), and used to direct how the cell works. The overall picture that emerges today from fields such as developmental, synthetic, and systems biology indicates that information processing in cells occurs through a hierarchy of genes regulating the activity of other genes through complex metabolic networks. There is an implicit semiotic character in this way of dealing with information,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…A shift in paradigm emerged when it was found that the natural and physiological polymer polyP, with its numerous high-energy phosphoanhydride bonds, stores metabolic energy which is released in the extracellular space during enzymatic degradation of the polymer [17,21]. This metabolic energy is required not only for endergonic biochemical reactions but also for driving energy dissipating compartmentation, protein folding and selfassembly processes [52]. In particular, the energy is needed for the building and maintenance of the organized extracellular fibrillar architecture [21].…”
Section: Discussionmentioning
confidence: 99%
“…A shift in paradigm emerged when it was found that the natural and physiological polymer polyP, with its numerous high-energy phosphoanhydride bonds, stores metabolic energy which is released in the extracellular space during enzymatic degradation of the polymer [17,21]. This metabolic energy is required not only for endergonic biochemical reactions but also for driving energy dissipating compartmentation, protein folding and selfassembly processes [52]. In particular, the energy is needed for the building and maintenance of the organized extracellular fibrillar architecture [21].…”
Section: Discussionmentioning
confidence: 99%
“… 53 This, combined with the heterogeneity of the reaction medium, self-assembly and phase separation processes, together with compartmentalization events, would enrich the space of possibilities for the emergence of the first self-sustaining autonomous systems (in a biological/metabolic relevant sense – see again ref. 12 and 24 ). In the context of this tutorial review, where various small cycles with prebiotic relevance have been discussed (see Schemes 4, 8 and 10 ), the networks resulting from their integration could be seen as a funnel that drives energy from abundant, constantly produced and highly reactive one-carbon precursors (formaldehyde, HCN, formamide) into self-sustaining protometabolic cycles of gradually increasing complexities ( Fig.…”
Section: Protometabolic Scenariosmentioning
confidence: 98%
“…This means that, with the help of fuelling molecules to promote the endothermic steps, together with catalysts to facilitate the slowly running ones, the kinetics and thermodynamics of the different reactions constituting the cycle should be coupled, in such a way that allows adapting the matter and energy balance of the system to the state of its close environment. 12,24 In this direction, a revolution is taking place in the capacity of chemists to manage out-of-equilibrium self-assembled systems and networks, [123][124][125][126][127] which makes this challenge potentially solvable in the future. A pertinent question, however, is whether the complexity of the TCA or the glyoxylate cycles would enable achieving an efficient dynamic coupling of their constituent transformations, in order to be run out of equilibrium.…”
Section: Robustness In Transition: Combining Kinetics and Thermodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, those suggestions explain not only the prebiotic synthesis of RNA and amino acids, but the transfer of information and heredity as a necessary byproduct. In a prebiotic environment, different molecular components possess different functions toward proto-cell formation, organizing itself as an autonomous chemical system(s) capable of chemical evolution [63]. It was demonstrated that mutually catalytic systems (MCS) can emerge and could maintain some structural integrity with oscillatory patterns [64].…”
Section: Systems Before Genetic Informationmentioning
confidence: 99%